2020
DOI: 10.1111/cge.13826
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum and polygenic score in German patients with familial hypercholesterolemia

Abstract: Autosomal-dominant familial hypercholesterolemia (FH) is characterized by increased plasma concentrations of low-density lipoprotein cholesterol (LDL-C) and a substantial risk to develop cardiovascular disease. Causative mutations in three major genes are known: the LDL receptor gene (LDLR), the apolipoprotein B gene (APOB) and the proprotein convertase subtilisin/kexin 9 gene (PCSK9). We clinically characterized 336 patients suspected to have FH and screened them for disease causing mutations in LDLR, APOB, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
2
10
1
Order By: Relevance
“…However, the difference in the polygenic score among FH/M− and FH/M+ individuals is modest both in our analysis and in other studies. 13 , 24 Moreover, the comparison between LIPIGEN subjects who were H/M− and the healthy subjects from the Whitehall II study showed that the LDL‐C level in the former is about 30% higher than in the latter group, despite comparable polygenic score values. These observations suggest that, in subjects with the FH phenotype but lacking a causative mutation (FH/M−), lipid levels may be determined by the interplay between genetic factors, including the polymorphisms evaluated in our study but also other unknown genetic determinants, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference in the polygenic score among FH/M− and FH/M+ individuals is modest both in our analysis and in other studies. 13 , 24 Moreover, the comparison between LIPIGEN subjects who were H/M− and the healthy subjects from the Whitehall II study showed that the LDL‐C level in the former is about 30% higher than in the latter group, despite comparable polygenic score values. These observations suggest that, in subjects with the FH phenotype but lacking a causative mutation (FH/M−), lipid levels may be determined by the interplay between genetic factors, including the polymorphisms evaluated in our study but also other unknown genetic determinants, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…2 is so small that it is impractical to classify hypercholesterolemic patients only by the score. [36] In addition, based on such continuous variables, it is not realistic to create a threshold to classify the patients as having so-called "polygenic FH". On the other hand, the effect sizes of rare genetic variations of the FH-gene are large enough to allow for classification of monogenic FH in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Common types of PVs in our study were missense, CNV, and frameshift variants (in this order of frequency). On the other hand, missense, frameshift, and nonsense variants were common in a recent German study 22) . Of note, herein, CNVs were detected in a considerable proportion (11.5%) of PV carriers, similar to Japanese data 9) .…”
Section: Clinical Predictors Of Pvsmentioning
confidence: 93%